The protective effect of Cerium dioxide against Acrylamide Toxicity in mature rat - Mohammed A. Qathee,; Salema Lafta Hassan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The current experiment was designed to investigate changes in rat intestine after Acrylamide (ACR) and Cerium dioxide (Ceo2) administration to investigate the protective properties of Ceo2. In this experiment 120 mature male rat are used were divided randomly for 6 groups, 20 for each. And they were consecutively: ACR (8 mg/kg), ACR +Ceo2 (8 and 35mg/kg), ACR +Ceo2 (8 and 15mg/kg),Ceo2(35mg/kg), Ceo2(15mg/kg), and D.W. group.finally, the intestinal samples were collected for biochemical, histopathological and immunohistochemistry investigations. The result shows significant elevation in Malondialdehyde (MDA) and depletion of glutathione (GSH). administration of ceo2 lead to significant improving biochemical, histopathological and immunohistochemistry results.Conclusion, the result of this study show the ameliorative effect of ceo2 against ACR toxic effect via excellent improving of biochemical, histopathological and immunohistochemical parameters.